NRAP-open-IAM: A flexible open-source integrated-assessment-model for geologic carbon storage risk assessment and management. (September 2021) - Vasylkivska, Veronika; Dilmore, Robert; Lackey, Greg; Zhang, Yingqi; King, Seth; Bacon, Diana; Chen, Bailian; Mansoor, Kayyum; Harp, Dylan
Abstract: Large-scale implementation of geologic carbon storage (GCS) to help reduce atmospheric greenhouse gas emissions requires stakeholder confidence that injected CO2 will remain contained and that potential subsurface environmental risks are acceptably small and manageable. The U.S. Department of Energy's National Risk Assessment Partnership (NRAP) has developed an open-source integrated assessment model (NRAP-Open-IAM) to help address questions about a potential GCS site's ability to effectively contain injected CO2 and protect groundwater and other overlying environmentally sensitive receptors. NRAP-Open-IAM allows a user to: (1) incorporate relevant site geologic and injection scenario data; (2) characterize important site features and events; (3) couple fast prediction models of various system components of the engineered geologic system; and (4) execute stochastic, dynamic simulation of whole GCS system performance, leakage risk assessment, and uncertainty quantification. NRAP-Open-IAM is available on GitLab (https://gitlab.com/NRAP/OpenIAM ), and is accompanied by multiple application examples and detailed user and developer guides. Highlights: NRAP-Open-IAM is an open-source integrated assessment model for characterization of geologic carbon storage system risks. The model is built on the open source concept to give advanced users the capability to freely modify the system. Example use cases suggest the practical utility of the tool to support stakeholder risk management decisions. The tool capabilities enable researchers to perform stochastic analysis of containment effectiveness and impact to receptors.